Selective Charge Injection via Topological van der Waals Contacts for Barrier-Free p-Type TMD Transistors - Ghods, Soheil; Jang, Ho-Chan; Choi, Jun-Hui; Kim, Min Woo; Lee, Hyunjin; Kim, Tae-Hoon; Heo, Keun; Kwun, Hyung Jun; Lee, Taehun; Lee, Yoon Kyeung; Lee, Sang Hoon; Kim, Seung-Il; et al. (John Wiley & Sons Ltd., 2026)
The continued miniaturization of electronic and optoelectronic devices places stringent demands on contact engineering for 2D semiconductors, particularly for p-type materials, where achieving low-resistance contacts remains a critical challenge. While van der Waals (vdW) contacts offer a promising route for next-generation electronics, the impact of microscopic interfacial phenomena on device performance remains insufficiently understood. Here, how selective charge injection is revealed to be governed by key interfacial parameters between WTe2, a topological vdW contact, and both Se- and S-based transition metal dichalcogenide (TMD) channel materials. Through device measurements and first-principles simulations, it is shown that WTe2 forms an exceptional vdW contact with p-type MoSe2, exhibiting an ultralow Schottky barrier height (approximate to 7 meV), low contact resistance (approximate to 0.47 k Omega mu m), and high carrier mobility (373 cm2 V-1 s-1). This selective charge injection is attributed to a larger interlayer distance in WTe2/Se-based TMDs, which suppresses orbital overlap and preserves interface quality. These microscopic descriptors serve as essential design principles for future 2D electronic and optoelectronic systems.